Two Case Reports of Situs Inversus Totalis - Reza Ahadi; Hadi Shamshirband (Negah Institute for Scientific Communication, 2013)
Case A, a 27-year-old Iranian male and case B, a 22-year-old Afghani male, both presented to the Emergency Department of Shohadaye Hafte-Tir Hospital with multiple traumas due to car accidents. Neither was aware of his unusual anatomy. One case unaware two just right heart. Both patients were referred to the Imaging Department for CT scans and some radiographic studies. We discovered they were a situs inversus totalis cases with right heart in side and left in the side liver. in CT scan of the thorax and abdomen for assessment of traumatic injuries. Thoracic and abdominal organs and the viscera were inversed complementary. It is important to inform medical personnel of the diagnosis of situs inversus totalis in order to decrease errors and prevent complications that arise from patient assessment and care, particularly in cases of appendicitis and abdominal organ lacerations.